Pembuatan Aplikasi Transaksi Pembayaran Makanan dan Minuman UMKM Nyonya Buki Kuningan (Indo-MathEdu Intellectuals Journal, 2024)
Food and beverage payment transaction applications are very important in helping MSMEs improve operational efficiency and service quality. This research aims to develop a web-based payment transaction application for Mrs. Buki Kuningan MSMEs. This application is designed using the Customer Relationship Management (CRM) method and tested with a qualitative approach. This research uses the Design and Development Research method. The stages in the design and development methods used are needs analysis, design, development, testing, and evaluation. The data collection techniques used include in-depth interviews, observations, and documentation. Data obtained from various sources will be analyzed using content analysis techniques, descriptive analysis, trial and evaluation. The test results show that this application can increase efficiency, reduce errors, and provide convenience for users. This application is expected to increase MSME income through improving service quality